DUAL-TASK BALANCE CONTROL IN ADOLESCENT ATHLETES FOLLOWING CONCUSSION - Zaslow, Tracy (Orthop J Sports Med, 2020)
BACKGROUND: Previous research has identified deficient dual-task balance control at the time of return to play (RTP) and possible worsening after RTP in older adolescents/young adults with concussion. These findings have not been investigated in younger patients with concussion. HYPOTHESIS/PURPOSE: We hypothesized that concussed adolescents would have slower walking speed and increased medial-lateral (ML) center of mass (COM) movement, which would normalize by the time of RTP but worsen after resuming activity. METHODS: 13 adolescent concussion patients (7 male; age 10-17 years) were prospectively evaluated at their initial visit (IV) (mean 18, range 4-43 days post-concussion), at RTP clearance (mean 46, range 12-173 days post-concussion), and one month later (mean 26, range 20-41 days post-RTP) along with 11 controls (3 male) seen for similarly timed visits. Standing balance was assessed using range and root mean squared (RMS) COM motion in the anterior-posterior (AP) and ML directions during standing on both legs with eyes open while performing quiet standing, dual-task audio Stroop, side-to-side head turns, and side-to-side thumb tracking tasks. Dynamic balance was assessed using walking speed and COM ML range and velocity during walking alone and with side-to-side head turns and verbal fluency (reciting words starting with “F”) dual tasks. Patients were compared against controls using t-tests, and changes over time were evaluated using linear mixed-effects regression. RESULTS: During standing, patients had higher COM ML RMS than controls at IV during head turns and higher COM AP range during thumb tracking. COM ML motion decreased from IV to RTP (head turns range -6.5mm, p=0.058; head turns RMS -16.8mm, p=0.002; thumb range 9.2mm, p=0.012) and increased from RTP to 1 month follow-up (head turns RMS +10.0mm, p=0.040; Stroop RMS +8.4mm, p=0.086). Patients walked slower than controls at IV during all tasks, and COM ML range was higher in patients vs. controls during verbal fluency at IV and RTP. Walking speed increased from IV to RTP during verbal fluency (+7.8cm/s, p=0.044), from RTP to post-RTP in single task walking (+6.1cm/s, p=0.041), and at each successive visit during head turns (+6.0cm/s and +6.5cm/s, p<0.07). COM ML range also decreased in patients from IV to RTP with verbal fluency (-14.7mm, p=0.011) and from RTP to post-RTP in single task walking ( 4.0mm, p=0.061). CONCLUSION: Adolescent concussion patients had deficits in static and dynamic balance control at initial presentation. This tended to improve by RTP and only worsened post-RTP for dual-task ML control during standing, suggesting that current conservative treatment protocols are appropriate.